(untitled) - Eastwood, John (Oxford, NY, 1999)
The book consists of 153 units, each on a grammatical topic. The units cover the main areas of English grammar. Special attention is given to those points which are often a problem for learners: the maining of the different verb forms, the use of the passive, conditionals, prepositions and so on.
Keywords: English grammar,English grammar,English language; Problems, exercises, etc,Study and teaching,Textbooks for foreign speakers